Current indications for low level laser treatment in maxillofacial surgery: a review. Issue 4 (April 2015) - Doeuk, C.; Hersant, B.; Bosc, R.; Lange, F.; SidAhmed-Mezi, M.; Bouhassira, J.; Meningaud, J.P.
Abstract Low level laser treatment (LLLT) is currently being used for various disorders, but with no convincing scientific evidence. Most recently we have noticed an increase in published randomised controlled trials (RCTs) that have focused on its applications in wound healing, scarring, disorders of the temporomandibular joint (TMJ), oral mucositis, and dental pain. Our aim therefore was to assess the scientific evidence about its current efficacy in maxillofacial surgery. We reviewed PubMed from January 2003 to January 2013 using the key phrase "low level laser treatment". Our inclusion criterion was intervention studies in humans of more than 10 patients. We excluded animal studies and papers in languages other than English, French, and German. We found 45 papers that we screened independently. The resulting full texts were scrutinised by two authors who awarded a maximum of 5 points using the Jadad scale for assessing the quality of RCT, and extracted the data according to sample size, variables of LLLT, the authors' conclusions, and the significance of the result. LLLT seems to be effective for the treatment of oral mucositis after treatment for head and neck cancer. However, it cannot yet be considered a valid treatment for disorders of the TMJ. It seems to improve gingival healing, and myofacial and dental pain.